Profil Sensori Minuman Yuzu (Citrus junos) Komersial - Lani Nurlela; Tjahja Muhandri; Dede Robiatul Adawiyah; Saraswati Saraswati (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
The yuzu product development process in general was related to the level of consumer preference or acceptance which could not be separated from the sensory aspect. The purpose of this study was to obtain a map of the sensory profile characteristics of the ideal product, to identify the sensory and emotional profile characteristics, as well as to observe the correlation between sensory attributes and preference for yuzu drink based on consumer perceptions. The methods used included consumer surveys, ideal profile methods, and check-all-that-apply (CATA) as consumer-based methods. The consumer survey involved 108 respondents to assess general consumer preferences. The sensory evaluation panel consisted of 47 consumer panelists. The samples for sensory evaluation included 4 commercial yuzu beverage products available in Jakarta. The results of ideal profile mapping for yuzu beverage products with codes A, B, C, and D indicated that product A closely matched the ideal sensory profile, with sensory attributes of sweetness, acidity, freshness, citrus, and bitterness. The yuzu drink samples with codes A and C provided the same distinctive sensory attributes both in the mouth and upon swallowing, with their respective distinctive attributes being sweetness and freshness. The sweetness and freshness were correlated with consumer preferences (overall liking) when the product was in the mouth, and the freshness was correlated with preferences when the product was swallowed. The emotional profile mapping results revealed that consumers favored products associated with the "pleasure" emotion as found in product A and "relaxing" emotion as found in product D.